Experimental tomography setup for imaging of electrodynamic structure on millimeter waves - Vertiy, Alexey A.; Gavrilov, S. E.; Aksoy, Serkan; Voinovskiy, I. V.; Karaçuha, Ertuğrul (Institute of Electrical and Electronics Engineers Inc., 2000)
A tomographic setup has been developed for the millimeter wave band. Tomography images of the object cross-section were reconstructed using the frequency range 135.54-136.5 GHz. The developed software is based on the first-order diffraction tomography formulation. The system combines the possibilities of tomographs operating in "on passage" and "measurement under surface" regimes. The use of both these approaches will allow to create the millimeter wave tomograph providing the image reconstruction of the object under investigation. The new reduction method of the surface contribution in an image of subsurface objects is proposed and considered. The essence of the method consists in using leaky waves of a transmission line of electromagnetic energy, when the line is located close to a surface, for illumination of subsurface objects. The suggested version of tomography is orientated towards applications in industry, medicine, detection/identification of abandoned objects and other fields. © 2016 Elsevier B.V., All rights reserved.
25th International Conference on Infrared and Millimeter Waves, IRMMW 2000 -- Beijing -- 116684